Exciton Polaritons in Microcavities New Frontiers - Sanvitto, Daniele; Timofeev, Vladislav (Springer Series in Solid-State Sciences,, 2012)
In the past decade, there has been a burst of new and fascinating physics associated to the unique properties of two-dimensional exciton polaritons, their recent demonstration of condensation under non-equilibrium conditions and all the related quantum phenomena, which have stimulated extensive research work. This monograph summarizes the current state of the art of research on exciton polaritons in microcavities: their interactions, fast dynamics, spin-dependent phenomena, temporal and spatial coherence, condensation under non-equilibrium conditions, related collective quantum phenomena and most advanced applications. The monograph is written by the most active authors who have strongly contributed to the advances in this area. It is of great interests to both physicists approaching this subject for the first time, as well as a wide audience of experts in other disciplines who want to be updated on this fast moving field.